Positive impact of the legislation on organotins contamination in the marine environment of Hong Kong - Yan Jiang; Man Sze Kwok; Huiju Lin; Rainbow W.S. Leung; Shaopeng Xu; Juan C. Astudillo; Mengyang Liu; Kenneth M.Y. Leung (Environment International)
Since September 2008, the use of organotin compounds (OTs) on antifouling systems on seagoing vessels has been globally banned by the International Maritime Organisation due to their toxic effects to non-target marine organisms. However, the regulation enforcement varies by government, hindering its effectiveness in controlling OTs contamination. For example, the Hong Kong Special Administrative Government enacted related legislation in January 2017. This study, conducted from 2022 to 2023, aimed to assess whether this law and its enforcement had significantly reduced OTs contamination in Hong Kong’s marine environment. The results showed significant reductions in concentrations of butyltins (BTs) in seawater and total OTs in the rock shell Reishia clavigera from 2010 to 2023, though only dibutyltin (DBT) decreased in sediment. Triphenyltin (TPT) was identified as the predominant compound in all matrices, with levels correlating positively with shipping activities. Imposex levels in R. clavigera also significantly decreased, as indicated by the vas deferens sequence index and the proportion of sterile female compared to 2010 and 2015. A probabilistic risk assessment based on tissue burden of tributyltin (TBT) and TPT in R. clavigera suggested that current TBT levels no longer had significant adverse effects on the gastropod, while TPT could impact 68% of their populations. Over a five-year period since the legislation, substantial reductions in BTs in coastal waters, and overall OTs in rock shells were observed, but TPT persisted at concerning levels. Continued risk management measures and regular monitoring are crucial to further mitigate TPT contamination in Hong Kong waters.